Correlations and Regression of the Initial and Final Sound on Reading Words in the Slovenian Language - Ropič Kop, Marija (Revija za elementarno izobraževanje, 2022)
The level of pupils’ acquired phonological awareness at the beginning of the 1st grade of primary school presupposes a high probability of ability to perform initial reading. The purpose of the study was to check the correlation and regression between the initial and the final sound and reading words in the Slovenian language. Accordingly, 192 first-grade pupils were included in the sample. The purpose of the study was to check the correlation and regression between the initial and the final sound and reading of the words. The importance of the findings highlights the promotion of voice awareness in kindergarten.
Keywords: phonological awareness, initial/final sound, word reading, kindergarten, 1st grade